Web-based e-learning environment - Milan Miˇsoviˇ (Journal of Telecommunications and Information Technology, 2003)
Using a progressive information technologies for development of web-based courses and their administration brings a lot of practical and theoretical problems. We know web course problem is only small solution concerning construction of a large entire web-based e-learning environment. One of a practical problem is how to construct web-based electronic courses that have to meet international AICC standards. Implementation of such strict statements resulted in a lot of small or larger difficulties if we had used an elementary HTML editor. Using a~special web course oriented editors can absolutely solve this problem. The second problem is construction of the web-based e-learning application that can administrate such web courses and takes into consideration AICC regulations. Development of such web applications is founded on the latest web technologies. This article introduces one approach to the modeling of the two most important components (web-based course, web-based application) of the web-based e-learning environment, convenient for Military Academy in Brno and Czech army. The article outlines the structure of web subject, e-learning environment and their implementation. The LMS`s structure and its functionality, based on a snaps algebra, belong to important results of the article.